Individual growth of Heleobia piscium in natural populations (Gastropoda: Cochliopidae) from the multiple use natural Reserve Isla Martin Garcia, Buenos Aires, Argentina - Martin, Stella Maris (2008)
The present work analyses the individual growth of Heleobia piscium in natural conditions in coastal drainage channels of the Multiple Use Natural Reserve Isla Martín García, Buenos Aires, Argentina. Isla Martín García is located in the Upper Río de la Plata, to the south of the mouth of the Uruguay river (34deg; 11′ 25″ S and 58° 15′ 38″ W). Monthly collections were made from July 2005 to July 2006 in the eastern part of the island (Arena Beach). The population of H. piscium showed a complex and dynamic structure of sizes during a long period of the annual cycle. Two cohorts could be detected. The Bertalanffy growth equation was: Lt = 6 (1-e -1.85 (t+0.38)) and Lt = 3.9 (1-e -0.19 (t+4.84)) for cohorts 1 and 2, respectively. The pattern of population growth displayed a staggered model, where the greatest growth is observed during the summer. The reproductive period occurred during six months, from the beginning of summer to middle of fall. Based on only one reproductive effort, this pattern is not similar to that of other cogeneric species already studied.